Intraocular injection of KH902 alleviates retinal hypoxia in a mouse model of oxygen-induced retinopathy - Yang, Ning; He, Xuejun; Zhang, Ningzhi; Xing, Yiqiao (Archives of Biological Sciences, 2021)
Paper description: KH902 (conbercept) is a novel anti-angiogenic agent. KH902 was injected intravitreally to analyze its effect on retinal hypoxia and neuroretinal structure in the oxygen-induced retinopathy (OIR) mouse model. Intravitreal injection of KH902 inhibited the formation of retinal neovascularization in OIR at postnatal day (P17). Intravitreal injection of KH902 had a significant effect on remitting the retinal hypoxia both at P14 and P17. Intravitreal injection of KH902 did not damage the neuroretinal structure at P17 in OIR. Intravitreal injection of KH902 should be safe and effective in restraining ocular angiogenesis and improving the retinal hypoxic condition. Abstract: Inhibition of vascular endothelial growth factor (VEGF) has been widely applied in anti-neovascularization therapies. As a novel anti-VEGF agent, KH902 (conbercept) is designed to restrain pathological angiogenesis. However, the effects of KH902 on retinal hypoxia have not been well studied. In a mouse model of oxygen-induced retinopathy (OIR), we assessed retinal hypoxia at postnatal days 14 (P14) and P17, as well as retinal neovascularization (RNV) at P17. In addition, we evaluated the protein level of VEGF and galectin-1 (Gal-1). Changes of the neuroretinal structure were also examined. Our results indicated that KH902 could remit retinal hypoxia in OIR at P14 and P17, which was an exciting novel finding for KH902 function. Additionally, we confirmed that KH902 markedly reduces RNV. Our results indicated that administration of KH902 downregulated VEGF expression, as well as Gal-1. Damage of neuroretinal structure after KH902 injection was not observed, which was also an encouraging result. Our study suggests that KH902 plays a role in alleviating retinal hypoxia and that it could be used for the treatment of other neovascular ocular diseases.